Das (Zusammen-)Spiel von Raum und spektraler Präsenz in der Fotografie Juan Rulfos (apropos [Perspektiven auf die Romania], 2025)
Juan Rulfo’s narrations are haunted by so many ghosts that the characters themselves can sometimes hardly distinguish whether they belong to the living or the world of the dead. This is well known and has been sufficiently analyzed. However, the spectral has also found its way into Rulfo’s far less researched photographic work and thereby decisively shapes – narrows or extends – its pictorial space. Nonetheless, Rulfo’s photographs take on a completely different dimensionality and plasticity; they constantly go beyond any kind of mere reproduction: the in-visible becomes present. This article studies the techniques that Juan Rulfo uses to visualize ghostly elements in his photographs (on a visual and auditive level). It will also include how the viewer’s gaze is directed and how the illusion of what is presumedly seen is inherent to the image. Yet, this is not just generated through specific medial methods, but also – that is my argument – through textual techniques that become a model for visual ‘phantasmagoric images.’
Keywords: photography; Juan Rulfo; spectrality/spectral; threshold; space